The assessment of physical risk taking: Preliminary construct validation of a new behavioral measure - Edward A. Smith (Public Library of Science (PLoS), 2021)
Risk taking is a complex heterogeneous construct that has proven difficult to assess, especially when using behavioral tasks. We present an exploratory investigation of new measure–the Assessment of Physical Risk Taking (APRT). APRT produces a variety of different outcome scores and is designed as a comprehensive assessment of the probability of success and failure, and magnitude of reward and punishment of different types of simulated physically risky behaviors. Effects observed on the simulated behaviors are hypothesized to reflect similar effects on real world physical risks. Participants (N = 224) completed APRT in a laboratory setting, half of whom had a 1.5 s delay interposed between button presses. Exploratory analyses utilizing generalized estimating equations examined the main effects and two-way interactions among five within-subject factors, as well as two-way interactions between the within-subject factors and Delay across four APRT outcome scores. Results indicated that Injury Magnitude and Injury Probability exerted stronger effects than any of the other independent variables. Participants also completed several self-report measures of risk taking and associated constructs (e.g., sensation seeking), which were correlated with APRT scores to assess the preliminary convergent and divergent validity of the new measure. After correcting for multiple comparisons, APRT scores correlated with self-reported risk taking in thrilling, physically dangerous activities specifically, but only for those who did not have a delay between APRT responses. This promising exploratory investigation highlights the need for future studies comparing APRT to other behavioral risk taking tasks, examining the robustness of the observed APRT effects, and investigating how APRT may predict real-world physical risk taking.